(3JQGLe QhGI GdMOjKs - (3GdcfGfj, GdYSbdGfj, CHh GdaVd, GHf MLQ, TgGH GdOjf, CMeO Hf Ydj Hf eMeO, J (B825 (3g`s
(3ChdgG (B:s
... (3EHQGgje Hf jSGQ Hf gGfF GdfXGe CHh ESMGb GdHUQj ehdi Hfj HMjQ Hf GdMGQK Hf YHGO GdVHYj ef QDhS GdeYJRdI eJge HGdRfObI hcGf TGYQG COjHG HdjZG hdg cJH cKjQI aj GdGYJRGd hGdadSaI PcQgG GdfOje (B...s
(3BNQgG (B:s
..(3bGd eMeO Hf ESMGb GdfOje cGf YGQaG HUfGYI GdcdGe dg ajg eUfaGJ cKjQI hcGf ef CUMGH LYaQ Hf eMeO GdUGOb heGJ HYO fcHI GdHQGecI HeOjOI eSJJQG hjbGd YGT Edi NdGaI GdeCehf (B..s
(3JHUQI GdYfhGf (B:s
(3efJbi ef dSGf GdejRGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\178s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs